2003
DOI: 10.1002/art.11224
|View full text |Cite
|
Sign up to set email alerts
|

Can we accurately predict the development of rheumatoid arthritis in the preclinical phase?

Abstract: Local interactions between (bio)chemicals and biological interfaces play an important role in fields ranging from surface patterning to cell toxicology. These interactions can be studied using microfluidic systems that operate in the “open space”, that is, without the need for the sealed channels and chambers commonly used in microfluidics. This emerging class of techniques localizes chemical reactions on biological interfaces or specimens without imposing significant “constraints” on samples, such as encapsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 56 publications
(78 reference statements)
1
36
0
1
Order By: Relevance
“…These sites become potential targets for IgG antibodies (53). Recent studies have suggested that the target epitopes in synovium are citrullinated vimentin or variants of the α and β chains of fibrin that have been subjected to posttranslational deimination (50,53,(56)(57). Deposits of fibrin and fibrin-related extracellular and intracellular deposits have long been recognized in inflamed rheumatoid synovium (58).…”
Section: Citrullinated Proteins Link Rheumatoid and Periodontal Inflamentioning
confidence: 98%
“…These sites become potential targets for IgG antibodies (53). Recent studies have suggested that the target epitopes in synovium are citrullinated vimentin or variants of the α and β chains of fibrin that have been subjected to posttranslational deimination (50,53,(56)(57). Deposits of fibrin and fibrin-related extracellular and intracellular deposits have long been recognized in inflamed rheumatoid synovium (58).…”
Section: Citrullinated Proteins Link Rheumatoid and Periodontal Inflamentioning
confidence: 98%
“…Routine screening with a high sensitivity RF IgM ELISA and anti-CCP tests 31,32 , followed by isotype determination 5,8,33 , may lead to early diagnosis of RA even before the onset of clinical symptoms. For those very likely to have or develop RA, early diagnosis may change the outcome and may drastically reduce the cost of treatment 23,34 . Based on the data presented here and previously 5,8,10,14,15,19,31,32,33 , an algorithm is proposed for the most efficient use of RF test by ELISA in the diagnosis of RA ( Figure 5).…”
Section: Rheumatologymentioning
confidence: 99%
“…As pointed out by Majka and Holers [54], such studies raise the important clinical issue of identifying subjects in a stage of preclinical autoimmunity in RA, as is seen with type I diabetes mellitus. Autoimmune diseases such as RA may exhibit three phases during their development: 1) a state of susceptibility resulting from genetic risk factors that predispose to the loss of self tolerance; 2) the transition to a state of autoreactivity with autoantibody production not yet associated with clinically apparent disease, and 3) clinically apparent disease characterized by immune-mediated tissue destruction [54].…”
Section: Anti-cyclic Citrullinated Peptide Antibodiesmentioning
confidence: 97%
“…Autoimmune diseases such as RA may exhibit three phases during their development: 1) a state of susceptibility resulting from genetic risk factors that predispose to the loss of self tolerance; 2) the transition to a state of autoreactivity with autoantibody production not yet associated with clinically apparent disease, and 3) clinically apparent disease characterized by immune-mediated tissue destruction [54]. It remains to be determined whether the early appearance of RF and anti-CCP autoantibodies in RA represents a primary loss of tolerance to self antigens or a secondary response to subclinical tissue injury with exposure to novel or abundant autoantigens [54].…”
Section: Anti-cyclic Citrullinated Peptide Antibodiesmentioning
confidence: 99%